2020
DOI: 10.1016/j.heliyon.2020.e03728
|View full text |Cite
|
Sign up to set email alerts
|

Comparing blood versus tissue-based biomarkers expression in breast cancer patients

Abstract: Molecular markers have been used as a tool for diagnostic approaches, staging, and evaluation of therapeutic responses in patients with cancer. Cancer molecular markers can also help clinicians to make decision on therapy and prognosis evaluation at the time of diagnosis. In the early diagnosis of breast cancer (BC), estrogen and progesterone receptors (ER/PR) expression levels should be determined through immunohistochemistry (IHC). In molecular genetics, there are some important tissue-based markers that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The biomarkers for immunotherapy patient selection and prognosis prediction were not able to follow the speed and success of drug development and indication expansions [ 33 ]. Most candidate biomarkers involve tumor molecular characteristics and are subject to several limitations, including the one-dimensional nature, need for biopsy, and cost issues [ 34 , 35 ]. The compound prognostic scores based on simple clinical and laboratory parameters have recently gained significant interest for prognosis prediction in ICI-treated patients [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers for immunotherapy patient selection and prognosis prediction were not able to follow the speed and success of drug development and indication expansions [ 33 ]. Most candidate biomarkers involve tumor molecular characteristics and are subject to several limitations, including the one-dimensional nature, need for biopsy, and cost issues [ 34 , 35 ]. The compound prognostic scores based on simple clinical and laboratory parameters have recently gained significant interest for prognosis prediction in ICI-treated patients [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these unexpected results are probably due to systemic αKlotho possibly not representing the local production of Klotho. Other publications have already demonstrated that biomarkers such as carcinoembryonic antigen, ERβ, cytokeratin 19 and c-Myc present in serum do not represent the production in a tumor microenvironment ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood collection is a non-invasive procedure and has been used for supporting diagnostics and/or monitoring circulating biomarkers. For instance; cancer antigen 125 (CA-125) for ovarian cancer [ 40 ]; CA-11-19 for colorectal cancer [ 41 ], CA-19-9 for lung cancer [ 42 ], and CA-15-3 for breast cancer [ 43 ], are well established markers in clinical practice. Circulating tumor DNA (ctDNA), tumor-derived cell-free DNA, may be promising in diagnosis of cancer and/or monitoring of relapse or progression [ 44 ].…”
Section: Precautions Of Data Output From Sequencingmentioning
confidence: 99%